DIFUSI NORMA GLOBAL KESETARAAN GENDER DI KOREA SELATAN TAHUN 2015-2023 - Octaviyanti Putri; Ani Widyani Soetjipto (Indonesian Journal of International Relations, 2025)
This research discusses the diffusion of global gender equality norms in South Korea through the analysis of the Norm Diffusion theory by Martha Finnemore and Kathryn Sikkink. The main focus is on how the gender equality norms initiated by the Convention on the Elimination of All Forms of Discrimination Against Women (CEDAW) are implemented in South Korea. Despite ratifying CEDAW in 1984, South Korea still faces significant challenges in achieving gender equality, largely due to strong patriarchal and Confucian values. This study identifies that the diffusion of gender equality norms is hindered by local political opportunity structures and weak grassroots movement support. Additionally, low publicity and awareness of CEDAW among the public and cultural barriers slow down the process of norm cascade and internalization of gender equality norms. The study concludes that to improve the acceptance and implementation of gender equality norms in South Korea, there needs to be significant changes in societal attitudes and more proactive government policies